The Most Common Injuries, Prevention Strategies and Health Benefits of Playing Padel - Sadok, Aleksandra; Kubas, Wojciech; Białek, Aleksandra; Karczewski, Jakub; Ryń, Kamila; Niemcewicz, Wojciech Jan; Koźlicka, Aleksandra; Klajda, Jakub; Czerniakowski, Mikołaj; Gorczyca, Zuzanna (Quality in Sport, 2026)
This article shows a comprehensive analysis of the risks and benefits associated with playing padel. The article presents the prevalence and etiology of common injuries, while also delineating the salutary effects of engaging in the sport. Padel is a rapidly expanding racket sport that combines elements of tennis and squash. It offers accessibility and entertainment for a wide range of participants. Its unique biomechanical demands, characterized by repetitive upper limb movements, sudden changes of direction, and limited playing space, predispose players to a variety of acute and overuse injuries. The most common issues involve the shoulder, elbow, lower limbs, and, increasingly, ocular structures. Effective injury prevention requires a holistic approach that integrates proper warm-up, progressive load management, stabilization and proprioceptive training, and the use of appropriate equipment. Rehabilitation strategies should be comprehensive, combining conservative treatment with modern functional methods to ensure safe return to play and diminish the risk of recurrence. A deeper understanding of injury mechanisms and tailored preventive programs will be essential to support the sustainable development of padel and safeguard the health of its rapidly expanding player base. This review aims to summarize the most frequent injuries observed in padel players, including both acute trauma and overuse syndromes, and to analyze their underlying mechanisms and prevention strategies. Epidemiological data highlight common injuries to the shoulder, elbow, ankle, and knee, often linked to repetitive motions and rapid directional changes. The review discusses current recommendations for injury prevention and rehabilitation and includes health aspects of playing padel. Current evidence is largely cross-sectional, underscoring the need for longitudinal studies to clarify long-term health effects, optimize injury prevention, and evaluate outcomes in older and clinical populations.